Site demands and some quantitative and qualitative characteristics of Persian Oak (Quercus brantii Lindl.) in Chaharmahal & Bakhtiari Province (western Iran) - Mahmood Talebi; Khosro Sagheb-Talebi; Hasan Jahanbazi (تحقیقات جنگل و صنوبر ایران, 2006)
This research was carried out at three sites, including lordegan, Ardal and Bazoft of Chaharmahl and Bakhtiari province, where the oak monna (Quercus branttii Lindl.) is the dominant tree species. First of all, forest types were sutdied, which Q. brantii was the main forest element. Tehn three sites at north west, west and south west of the province, where are the main habitats of Oak manna, were selected and 12 plots of 1000 m2 surface area were allocated at each site, including three land forms (valley, slope and ridge) and four main slope aspects (north, south, east, west). Overall, 36 plots were allocated and site demands, soil physical and chemical properties and tree quantitative and qualitative characteristics were studied at each plot. The results showed that the Oak manna is a light demanding species with highest distribution on south western slopes at 1800 to 2000 m. above sea level. Soil pH varied from 7.7 at soil surface to 7.85 at deep layers. Total nitrogen and organic matter of soil was good and its salinity was not significant. Most of the Oak trees had a coppice regeneration form (84, 2-78-6 %). Averagely, each tree produced four to five sprouts. This indicates a severe impact of human on Oak forests. Diameter and height of Oak trees varied between 13.8-19 cm and 4.3-5.2 m, respectively due to variation in land form.